Pemetaan Tingkat Kekerasan Pada Anak dan Perempuan Menggunakan Algoritma K-Medoids (Studi Kasus : P2TP2A DKI Jakarta) - Bella Nurseptia; Nina Sulistiyowati; Apriade Voutama (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Since 2018-2022 P2TP2A DKI Jakarta Province has recorded an increase in cases of violence against children and women. The lack of public awareness of the issue of violence is one of the factors in the increase in these cases. One of the efforts that can be made by the government to optimize handling, prevention and reducing the number of cases of violence is to classify and map areas based on the level of violence against children and women. This study uses the CRISP-DM methodology which consists of the stages of Business Understanding, Data Understanding, Data Preparation, Modeling, Evaluation, Deployment. The algorithm used to classify data on cases of violence against children and women in 2018-2022 is k-medoids. Determination of the number of clusters is carried out using 2 methods, namely the elbow method and the silhouette coefficient. The result of this study is the grouping of regions based on the level of violence against children and women visualized using QGIS tools. The results of the cluster evaluation show that the lowest DBI value is 1.484557, where the optimal number of clusters is 3 with the method of determining the number of k using the elbow method. Clustering results show that cluster 1 is an area with a low level of violence consisting of 6 sub-districts, cluster 2 is an area with a moderate level of violence consisting of 30 sub-districts, and cluster 3 is an area with a high level of violence consisting of 8 sub-districts